Detecting the most stable and best-performing genotypes by analysing on-farm experiments with ranking data across different environments and management practices - 1000FARMS Platform (2025)
This poster illustrates how tricot data can be leveraged to assess genotype × environment × management (GxExM) interactions, with the aim of identifying more context-responsive crop varieties. It emphasizes the use of simple ranking data and large datasets to uncover complex adaptation patterns. The study is part of 1000FARMS’ broader effort to make farmer-managed trials a valuable source of scientific insight.